Determinants of the interest rate pass-through of banks: Evidence from German loan products - Tobias Schlüter; Ramona Busch; Thomas Hartmann-Wendels; Sönke Sievers (Deutsche Bundesbank, 2012)
This article examines the loan rate-setting behavior of German banks for a large variety of retail and corporate loan products. We find that a bank's operational efficiency is priced in bank loan rates and alters interest-setting behavior. Specifically, we establish that a higher degree of operational efficiency leads to lower loan markups, which involve more competitive prices, and smoothed interest rate-setting. This study contributes to prior literature that has been suggesting this relationship but has produced mixed findings. For the German market this relationship is unexplored. By employing stochastic frontier analysis to comprehensively capture cost efficiency, we take the bank customers' perspective and demonstrate the extent to which borrowers benefit from cost efficient banking.
Keywords: G21; G28; 330; interest rate pass-through models; error correction models; bank efficiency; cost efficiency; stochastic frontier analysis